Children's Addictive Behavior in Watching Animation on Youtube, What is the Solution? - Indah Rohmiatun (Journal of Business, Social and Technology, 2025)
In this modern era, many entertainment media are easily accessible to children via Youtube. Along with the progress and evolution of educational knowledge and technology, the role of parents in early childhood education is very important. Parents need to understand and learn about every latest knowledge and technology in this era full of various challenges. Many parents do not realize that gadget addiction can be dangerous because it can damage children's mental and physical health. Some parents don't even realize when their children spend 3 hours or even the whole day watching YouTube without a break. Situations like this can indicate when the child has experienced addiction. Based on the results, researchers want to provide an understanding of parents related to children who are addicted to animated YouTube content using an interpersonal communication approach.  With parental guidance, the selection of animated content on the elements of learning methods and watching together actively can reduce the potential for excessive addiction and the weakness of watching negative animated content. The selection of animations such as Nussa and Rara as children's shows is an educational selection. This animation includes good character education, so it is suitable for shaping children's character if introduced early.